2001
DOI: 10.1111/j.1471-0528.2001.00067.x
|View full text |Cite
|
Sign up to set email alerts
|

The development of high venous velocity at the fetal umbilical ring during gestational weeks 11–19

Abstract: Objective To determine the occurrence of high venous velocities at the umbilical ring in the normal early second trimester, based on the assumption that a narrow umbilical ring may cause obstruction and increased venous blood velocity at the abdominal wall.Design Cross-sectional study. Setting Hospital antenatal clinic.Population One hundred and one low risk singleton pregnancies speci®cally recruited for the study.Methods Ultrasound was used at 11±19 weeks to determine the diameter and velocity in the umbilic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Skulstad et al . investigated the umbilical venous velocity increment at the fetal abdominal wall during gestational weeks 11–19 and demonstrated that the blood velocity was higher in the umbilical vein at the abdominal wall than in the free loop of the cord, especially after 13 weeks . On the other hand, a small tendency toward a reduced relative velocity increment at the umbilical ring occurring in association with increasing gestational age from 20 to 40 weeks of gestation has been reported .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Skulstad et al . investigated the umbilical venous velocity increment at the fetal abdominal wall during gestational weeks 11–19 and demonstrated that the blood velocity was higher in the umbilical vein at the abdominal wall than in the free loop of the cord, especially after 13 weeks . On the other hand, a small tendency toward a reduced relative velocity increment at the umbilical ring occurring in association with increasing gestational age from 20 to 40 weeks of gestation has been reported .…”
Section: Discussionmentioning
confidence: 97%
“…The velocity increment at the level of the umbilical ring was calculated as the difference between the velocity at the umbilical ring and that found in the free loop presented as the percentage of the velocity in the free loop, as reported by Skulstad Velocityincrementattheumbilicalring=venousvelocityatringvenousvelocityatfreeloop/venousvelocityatfreeloop%…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyper-coiled cord tends to lead to fetal hypoxia due to an external force such as labor or a fetal movement more often than a normal coiled cord [1]. Several studies have shown that hyper-coiled cords are correlated with poor perinatal outcomes such as low birth weight, meconium staining of amniotic fluid at birth and fetal growth restriction [2][3][4]. In our previous study of intrauterine fetal death after the second trimester, fetal death was found to be caused by a hyper-coiled cord in 25.9% (21/81) of cases.…”
Section: Introductionmentioning
confidence: 99%